The role of vowel length and pitch in Xhosa sentence type intonation - Ström, Eva-Marie Bloom (Stellenbosch Papers in Linguistics Plus, 2022)
This paper is a first study of intonation across different sentence types in Xhosa. A recent increase in intonation research of African languages, including Bantu, has shown that intonation involves the manipulation of several distinct prosodic features such as vowel length and voice, next to pitch (Downing and Rialland 2017a). Xhosa is a tonal language as many other African languages, meaning that the use of pitch for intonational purposes interacts with the use of lexical and grammatical tone. Moreover, other means are employed than pitch rise to distinguish different intonational phrases. For example, previous research shows that polar questions in Xhosa are indicated by reducing the lengthening of the penultimate vowel of a phrase, which is long in declaratives (Jones 2001). This paper expands on such previous studies and includes the intonation of different kinds of questions and focus constructions in order to sketch a more complete picture of Xhosa intonation. It shows that the manipulation of penultimate lengthening plays an important role in distinguishing different phrases, in combination with declination and final lowering of pitch. Also, devoicing the last vowel to a whisper indicates end of the intonation phrase. Understanding the interaction of tone, intonation and phonological phrasing is important for understanding the grammatical structure and discourse pragmatics of Bantu languages.